IMPLEMENTASI METODE COCOSO PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN HOTEL DI KABUPATEN BULELENG - Sandhisutra, Ida Bagus Ketut; Dewi, Desak Putu Eka Komala; Parwathi, Ni Luh Gede Putri Desta; Mahendra, Gede Surya; Desmayani, Ni Made Mila Rosa (Department of Information System Muhammadiyah University of Riau, 2024)
The Buleleng Regency, located in North Bali, is a strategic and attractive area for tourists. The combination of natural beauty, art, and culture has attracted many tourists, for recreational, business, and other purposes, making tourists plan to stay comfortably in the Buleleng Regency. However, with numerous hotel choices, tourists often find it confusing to select and find a hotel that suits their needs. To address this issue, this research provides a solution using a Decision Support System. The method chosen is the Combined Compromise Solution. There are 6 criteria that form the basis for assigning criteria weights: rental price, distance from the city center, star rating, overall rating, facilities & services, tourist area rating, and parking conditions. With 7 hotel alternatives in this study, the New Sunari Lovina hotel emerges as the best recommendation for tourists, with a preference score reaching 2.2999, followed by Banyualit Spa & Resort Lovina and Singaraja Hotel as the next recommendations.